STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF PODCAST IN IMPROVING ENGLISH SPEAKING SKILL - Eirene, Jessica; Luhriyani, Seny; Asfah, Indrawaty; Azhari, Ahmad; Sembiring, Surya Anantatama (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This study explores the students’ perceptions of using podcasts to improve their English-speaking skills at Business English Communication program. The study is motivated by the growing integration of technology in education, particularly in language learning, where podcast offer a flexible and engaging medium. Using a qualitative approach, the research investigated how students perceive the effectiveness, interest, and relevance of podcasts in enhancing their speaking abilities. Data were collected through in-depth interviews and analyzed to understand the perceived benefits and challenges. The findings indicate that students generally view podcasts positively, appreciating their convenience and the opportunity to hear authentic English. However, some challenges, such as accessibility and the need for self-discipline, were noted. The study contributes to the theoretical understanding of media-based learning and provides practical insights for educators and curriculum developers aiming to incorporate digital media into language instruction effectively.